New Set of Indicators to Measure Population Remoteness and Dispersion : Estimates for 100 Countries, with Detailed Analysis of Pacific Island Countries - Xia, Boer; Halstead, Imogen; Utz, Robert (World Bank, Washington, DC, 2020)
This paper defines three new indicators that capture the remoteness of local communities within a country context and the overall scale of population dispersion and settlement sparsity across a country. The paper also exploits the World Bank’s subnational geography database to estimate the geographical scale of population dispersion and dispersion-adjusted population sparsity for 100 countries around the world. The new indicators are evaluated and explored for several Pacific Island countries, which are often characterized as being remote (in a global context) and highly dispersed. However, within each Pacific Island country, there is enormous variation in the remoteness of individual communities and the extent to which communities are clustered or dispersed from one another, and these conditions can be related to communities' socioeconomic characteristics. The results reflect this. The paper empirically contextualizes the settlement patterns evident in the Pacific Island countries within a broader global context, highlighting the extreme degree of population sparsity in the Pacific, relative to all the other countries that are assessed.